The importance of shaving the zygomatic process during reduction malarplasty. Issue 8 (August 2016) - Lee, T.S.
Abstract: Reduction malarplasty surgery has become increasingly popular in recent years, especially in many East Asian countries. This is, in part, because many Asians consider a small, smooth, and feminine face to be more attractive and aesthetically desirable. Among the various reduction malarplasty methods, the L-shaped osteotomy technique, through intraoral and sideburn incisions, is now one of the most frequently performed surgical techniques. During the surgical procedure, it is important to shave the zygomatic process of the temporal bone through the sideburn incision. By carrying out this simple adjunctive procedure, several remarkable results can be achieved. The facial width is reduced, especially in those patients with protrusion of the posterior portion of the arch. The outward curvature of the zygomatic arch is changed to point inward. And finally, the bony step that originates from the medial repositioning of the zygomatic arch is reduced, resulting in decreased palpability.